Extra gene coding capacity of SARS-CoV-2 provides a virus engineering platform for in vitro and in vivo applications - Taksoo Kim; Asim Biswas; Sangam Kandel; Makoto Kuroda; Peter J. Halfmann; Yoshihiro Kawaoka (Proceedings of the National Academy of Sciences, 2026)
The genomic flexibility of orthocoronaviruses, including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is showcased by the presence of accessory genes, which vary in number among virus species and strains. Given this flexibility, the viral coding capacity can be artificially expanded to express a heterologous gene from the viral genome, thereby enabling the development of a viral vector platform. Here, we systematically explored the extra gene coding capacity of SARS-CoV-2 by inserting an extra reporter gene at every intergenic region in its genome. We revealed the entire scheme of its extra gene expression and identified a genomic location that stably expresses reporter genes while maintaining the wild-type viral phenotype. Using this construct, we developed a set of fluorescent and luminescent reporter SARS-CoV-2 viruses available for in vivo flow cytometry and in vitro antiviral screening. Flow cytometric analysis with these reporter viruses revealed cell type–specific dynamics of SARS-CoV-2 infection in the lung tissue of K18-hACE2 mice. Our findings offer a platform for SARS-CoV-2 genome engineering, providing a set of reporter viruses for research applications.